The Impact of Chronic Heat Stress on the Growth, Survival, Feeding, and Differential Gene Expression in the Sea Urchin Strongylocentrotus intermedius - Zhan, Yaoyao; Li, Jiaxiang; Sun, Jingxian; Zhang, Weijie; Li, Yingying; Cui, Donyao; Hu, Wanbin; Chang, Yaqing (Frontiers in Genetics, 2019)
Abstract To explore the impact of chronic heat stress on commercial echinoderms, the present study assessed the effects of chronic high temperature on the growth, survival, feeding, and differential gene expression in the sea urchin Strongylocentrotus intermedius cultured in northern Yellow Sea in China. One suitable seawater condition (20°C) and one laboratory-controlled high temperature condition (25°C) were set up. After 28 days incubation, our results showed that: (1) The specific growth, survival, and ingestion rates of S. intermedius reared under high temperature (25°C) decreased compared to those reared under optimal temperature (20°C) conditions; (2) comparative transcriptome analysis identified 2,125 differentially expressed genes (DEGs) in S. intermedius reared under high temperature (25°C) compared to those subjected to optimal temperature condition (20°C), which included 1,015 upregulated and 1,100 downregulated genes. The accuracy of the transcriptome profiles was verified by quantitative real-time PCR (qRT-PCR). Further Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways analyses revealed that these DEGs mainly enriched the functional categories of ribosome, protein processing in endoplasmic reticulum, and prion diseases. A total of 732 temperature-induced expressed genes, such as ATP5, heat shock protein 70, and heat shock protein 90, were identified as candidates that were closely correlated with heat resistance in S. intermedius. Differentially expressed transcription factors (TFs), such as AP-1, Fos, CREB, and ZNF, were also identified as potential regulators that regulate the molecular network that was associated with responses to heat stress in sea urchins. Observations in the present study provide additional information that improves our understanding of the molecular mechanism of temperate echinoid species in response to heat stress, as well as theoretical basis for the molecular-assisted breeding of heat-resistant sea urchins.